Komunikasi Pembangunan Partisipasi Membangun Objek Wisata Terhadap Peningkatan Ekonomi Masyarakat - Idawati (Medium: Jurnal Ilmiah Fakultas Ilmu Komunikasi, 2022)
Community participation in building tourism objects is one form of improving the economic welfare of the community, so that people have a better standard of living in the future. The city of Dumai is an industrial city known for its beautiful beaches, as an industrial city, of course the government through a program to touch people with advanced thinking patterns to build local tourism that they have with quite beautiful beach views. This study aims to find out how community participation is to build natural tourism objects to improve the economy. And what are the barriers to community participation. The theoretical approach used is the theory of "awareness" in development communication known as the theory of two-way communication. The method used in this research is a qualitative descriptive method of community survey, with the aim of seeing the participation. The results of this study prove that the level of community participation in tourism development is still low, due to several problems, assuming that development is the responsibility of the government, not having time availability, lack of willingness, the solution given is to provide guidance, inculcate the value of awareness, development planning, the importance of development.